Gut microbiota‐CRAMP axis shapes intestinal barrier function and immune responses in dietary gluten‐induced enteropathy - Zhengnan Ren; Li‐Long Pan; Yiwen Huang; Hongbing Chen; Yu Liu; He Liu; Xing Tu; Yanyan Liu; Binbin Li; Xiaoliang Dong; Xiaohua Pan; Hanfei Li; et al. (EMBO Molecular Medicine)
Abstract In the gut, cathelicidin‐related antimicrobial peptide (CRAMP) has been largely described for its anti‐infective activities. With an increasing recognition of its immune regulatory effects in extra‐intestinal diseases, the role of CRAMP in gluten‐induced small intestinal enteropathy celiac disease remains unknown. This study aimed to investigate the unexplored role of CRAMP in celiac disease. By applying a mouse model of gluten‐induced enteropathy (GIE) recapitulating small intestinal enteropathy of celiac disease, we observed defective CRAMP production in duodenal epithelium during GIE. CRAMP‐deficient mice were susceptible to the development of GIE. Exogenous CRAMP corrected gliadin‐triggered epithelial dysfunction and promoted regulatory immune responses at the intestinal mucosa. Additionally, GIE‐associated gut dysbiosis with enriched Pseudomonas aeruginosa and production of the protease LasB contributed to defective intestinal CRAMP production. These results highlight microbiota‐CRAMP axis in the modulation of barrier function and immune responses in GIE. Hence, modulating CRAMP may represent a therapeutic strategy for celiac disease.